Management of health and safety in the organization of worktime at the local level - Jeppesen, Hans Jeppe; Bøggild, Henrik (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'This study examines the consideration of health and safety issues in the local process of organizing worktime within the framework of regulations.' ' METHODS ': 'The study encompassed all 7 hospitals in one region of Denmark. Twenty-three semi-structured interviews were carried out with 2 representatives from the different parties involved (management, cooperation committees, health and safety committees from each hospital, and 2 local unions). Furthermore, a questionnaire was sent to all 114 wards with day and night duty. The response rate was 84%. Data were collected on alterations in worktime schedules, responsibilities, reasons for the present design of schedules, and use of inspection reports.' ' RESULTS ': 'The organization of worktime takes place in single wards without external interference and without guidelines other than the minimum standards set in regulations. At the ward level, management and employees were united in a mutual desire for flexibility, despite the fact that regulations were not always followed. No interaction was found in the management of health and safety factors between the parties concerned at different levels.' ' CONCLUSION ': 'The demands for flexibility in combination with the absence of guidelines and the missing dynamics between the parties involved imply that the handling of health and safety issues in the organization of worktime may be accidental and unsystematic. In order to consider the health and safety of night and shift workers within the framework of regulations, a clarification of responsibilities, operational levels, and cooperation is required between the parties concerned.
Keywords: hospital; participation; prevention; regulation; shift work; work environment